2010
DOI: 10.1007/s11104-010-0545-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus availability for three crop species as a function of soil type and fertilizer history

Abstract: Knowledge of the capacity of a soil to supply phosphorus (P), and the variation in the ability of different crops to access soil P, is critical to successfully managing P in modern cropping systems. Isotopic dilution techniques were used to examine the capacity of three contrasting soil types (Calcarosol, Vertosol and Chromosol) to supply P, and to compare the ability of three different crop species (wheat, chickpea and canola) to access P under both low and adequate P conditions. This was achieved by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Canola also took up more P than wheat at a given amount a P fertiliser, suggesting that canola roots have a greater ability to utilise soil P, at least in the soils used in those studies. Vu et al (2010) also found canola seedlings to be very responsive to P in a range of soils from Victoria. In northern New South Wales, canola often shows greater responses to P than wheat, and P nutrition is considered more critical in canola than in wheat (Serafin et al 2005).…”
Section: Phosphorus Requirements Of Different Cropsmentioning
confidence: 85%
See 2 more Smart Citations
“…Canola also took up more P than wheat at a given amount a P fertiliser, suggesting that canola roots have a greater ability to utilise soil P, at least in the soils used in those studies. Vu et al (2010) also found canola seedlings to be very responsive to P in a range of soils from Victoria. In northern New South Wales, canola often shows greater responses to P than wheat, and P nutrition is considered more critical in canola than in wheat (Serafin et al 2005).…”
Section: Phosphorus Requirements Of Different Cropsmentioning
confidence: 85%
“…The ability to use soil P and responses to P fertiliser can vary among different crop species, although the extent of the difference is influenced by soil type (Bolland et al 1999;Brennan and Bolland 2001;Bolland and Brennan 2008;Vu et al 2010).…”
Section: Phosphorus Requirements Of Different Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason might be the P transformation between different P pools. It is well known that soil labile P pools are quite well buffered via equilibrium with more stable P forms [18] [36] [37], and that it can take a few years of a change in management practice to produce significant changes in the labile pool amounts.…”
Section: Extractable Soil P and P Supply Ratementioning
confidence: 99%
“…Although both soils are alkaline throughout the profile, the Calcarosol tends to have greater pH at depth, sorbs less P in the surface layers and is coarser textured (Vu et al 2009(Vu et al , 2010. Although this coarser soil texture reduces its overall ability to store soil water throughout the profile during the fallow period preceding sowing, small rainfall events (<5 mm) are able to penetrate deeper into the soil surface layers where fertilisers are banded and root growth tends to be concentrated.…”
Section: Tillage Systems and Nutrient Distributionmentioning
confidence: 99%